Student Satisfaction Regarding Service Quality at Ethiopian Public Higher Education Institutions: A Case Study (Journal of Student Affairs in Africa, 2021)
The quality of services rendered to stakeholders at Higher Education Institutions (HEIs) is of critical importance to the esteem of these institutions. Perceptions of the quality of such services can be measured in various ways. This study assesses the extent of service quality as evaluated in students' satisfaction with services received at Ethiopian HEIs. To this end, data was collected from final-year undergraduate students at Ethiopian Public Higher Education Institutions (PHEIs). The Service Quality (SERVQUAL) questionnaire was administered. The collected data was analysed using the methodology of the Importance-Performance Analysis (IPA) model. Findings indicated that themajority of the elements that constitute attributes of service quality were perceived by students to be very poor. This is reflected in low satisfaction scores. It is recommended that HEIs identify those service areas that have high perceived importance scores and low perception scores on service-experience in order to redeploy some of the resources and implement measures to improve service quality.
Keywords: Importance-Performance Analysis (IPA) model; public higher education institutions in Ethiopia; service quality; service quality improvement; student satisfaction